2010
DOI: 10.1002/mame.201000252
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Polymerization Surface Modification of Carbon Black and its Effect in Elastomers

Abstract: Surface modification of carbon black by plasma polymerization was aimed to reduce its surface energy in order to compatibilize the filler with various elastomers. A fullerenic carbon black was used for the modification process. Thermogravimetric analysis, wetting behavior with liquids of known surface tension, TEM and TOF‐SIMS were used to characterize the carbon black before and after modification. The state of plasma‐coated carbon black in rubber was studied by means of conductivity measurements. The behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It is clear that the chemically inert nature of the exposed graphene structures on the surfaces of MWCNTs was responsible for the decreased surface energy of the PA6-MWCNT composites with increased MWCNT content [21]. However, the increased CB content in the PA6-MWCNT-CB composites from 1 to 5 wt.% apparently decreased the water contact angle of the composites from about 85.6° to 57.8° ( Figure 2) because the presence of hydroxyl or oxide groups on the CB surfaces makes the composites more hydrophilic than the pure PA6 [22]. The field emission scanning electron micrographs in Figure 3 show the fractured cross sections of the PA6 matrix composite samples with different carbon filler contents.…”
Section: Surface Activity and Morphology Of The Pa6 Matrix Compositesmentioning
confidence: 80%
“…It is clear that the chemically inert nature of the exposed graphene structures on the surfaces of MWCNTs was responsible for the decreased surface energy of the PA6-MWCNT composites with increased MWCNT content [21]. However, the increased CB content in the PA6-MWCNT-CB composites from 1 to 5 wt.% apparently decreased the water contact angle of the composites from about 85.6° to 57.8° ( Figure 2) because the presence of hydroxyl or oxide groups on the CB surfaces makes the composites more hydrophilic than the pure PA6 [22]. The field emission scanning electron micrographs in Figure 3 show the fractured cross sections of the PA6 matrix composite samples with different carbon filler contents.…”
Section: Surface Activity and Morphology Of The Pa6 Matrix Compositesmentioning
confidence: 80%
“…This was determined by tensile strength measurements [97,98]. Mathew et al [99] found that there was less aggregation and a decrease in the cross-linking density of the polymer, which in turn, leads to a decrease in the hardness of rubber. In the case of BCB or NCB, the hardness increases, and the increased dispersion force of the CBs strengthens the filler and improves the cross-linking density of the polymer.…”
Section: Rubber/carbon Blacks After Plasma Treatmentsmentioning
confidence: 99%
“…Nowadays, the laboratory uses low‐temperature plasma to treat materials or their surfaces. Its advantage is that the electrons in the microstate have very high energy, which can make the treated material molecules in an excited state, and the ambient temperature can be kept at a lower temperature during the treatment process, with minimal loss on the material surface 22–26 …”
Section: Introductionmentioning
confidence: 99%